RELASI AGAMA DAN POLITIK: PREFERENSI POLITIK PEMILIH MILLENIAL DI PONOSAKAN BELANG, DALAM PILKADA SULAWESI UTARA TAHUN 2020 - Rohit Mahatir Manese; Budi Nurhamidin (Ri'ayah: Jurnal Sosial dan Keagamaan, 2021)
This study explains the relationship between religion and politics in the contestation of democracy in Indonesia. In this case, the 2020 Regional Head Election in North Sulawesi, especially in the village of Ponosakan Belang. By using a qualitative-descriptive research method and reading using a sociological and psychological approach. This research found that in the 2020 Pilkada in North Sulawesi there was one candidate who was Muslim and this is a preference for millennial voters in Ponosakan Belang to choose that candidate. The reading uses sociological theory, the preference is to choose an Islamic leader because of the same beliefs and religions. Psychologically, the presence of millennia voter political preferences is due to the issue of using Islamic symbols. The author's thesis is that in an electoral democracy, the relationship between religion and state is difficult to separate, religion becomes an important consideration in politics.